MODEL PENINGKATAN KINERJA GURU MELALUI KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI YANG DIMEDIASI KEPUASAN KERJA (Studi pada Guru SMAN 1 Kejayan dan SMAN 1 Lumbang Kabupaten Pasuruan) - Tantrianingrum, Trisnurini; Suci, Rahayu Puji; Mas, Nasharuddin (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to obtain empirical evidence of transformational leadership abilities and motivation in encouraging improvements in teacher performance, both directly and through the mediation of job satisfaction. This type of research is quantitative with the SEM-SmartPLS method. Data was obtained through questionnaires distributed to 82 teachers of SMAN 1 Kejayan and SMAN 1 Lumbang, Pasuruan Regency. The sample is determined by census or saturated sample. Empirical evidence shows that both transformational leadership and motivation are able to encourage increased teacher performance, both directly and through the mediation of job satisfaction. Job satisfaction can act as a strong mediator